Kritik Sosial Dalam Antologi Puisi Aku Ingin Jadi Peluru Karya Wiji Thukul (Sebuah Tinjauan Sosiologi Sastra) - Kuncoro Hadi, Panji (Jurnal Pendidikan, 2009)
The objectives of this research are: 1) to identify whatever themes are proposed in poetry anthology AIJP by Wiji Thukul, 2) to describe social criticisms in Wiji Thukulâs poetries, 3) to describe Wiji Thukulâs social criticisms in poetry anthology AIJP by Wiji Thukul, and 4) to identify ethic, moral, behavioral values in poetry anthology by Wiji Thukul.Â Â Â Â Â Â Â Â Â Â Â Â  This research is carried out under qualitative-descriptive method by content analysis. Content analysis method is applied by literary structure and sociology. Author sociological approach is also brought in to depict the authorâs background. The data are drawn under purposive sampling technique bearing 5 titles out of 136 poetries available in poetry anthology by Wiji Thukul which represent the social criticism theme. Data validity is assured by the use of theoretical triangulation by structural and sociological theories.Â Â Â Â Â Â Â Â Â Â Â Â  The analysis brings about conclusions as follows: first, under sociological criticism perspectives of society, Wiji Thukul poses two aspects: 1) social protest, and 2) social realism. The two aspects are obviously belong to the âhomeâ of social criticism by literary media. Second, ethic, moral, and behavioral values belong to the lower social class occupied as: labour, padicab drivers, trash-collectors etc.Â Key wordsÂ  :Â  Social Criticism, Poetry Anthology Aku Ingin Jadi Peluru by Wiji Thukul, and Literary Sociology